Organic acid pretreatment of oil palm trunk biomass for fermentable xylose production. Issue 2 (January 2020) - Bukhari, N A; Jahim, J M; Loh, S K; Harun, S; Nasrin, A B
Abstract: Green alternatives to chemical pretreatment in hydrolysing hemicellulose for efficient biorefineries are very much sought-after. In this study, we aimed to determine the effectiveness of several organic acids in hydrolysing hemicellulose of oil palm trunk biomass (OPTB) to form fermentable xylose. Various organic acids (citric acid, formic acid and oxalic acid) of different concentration (0.5-5.0%) were assessed to find a suitable catalyst in hydrolysing OPTB for reaction time (15-120 min) at a fixed temperature (120°C), aiming for high xylose selectivity. Of these, oxalic acid was shown the most effective in solubilizing hemicellulose from OPTB, producing a maximum xylose yield of ∼70% at the optimum catalyst concentration of 5.0% (w/v) for 120 min. The main components in the hemicellulosic hydrolysate were xylose, 16.26±0.30 g/L; glucose, 2.11±0.04 g/L; arabinose, 0.19±0.05 g/L; acetic acid, 5.59±0.07 g/L and trace amount of furfural and hydroxylmethylfurfural (HMF). The resulting xylose recovery was comparable to the conventional pretreatment using dilute sulphuric acid, thus provides an alternative approach of biomass pretreatment for process improvement. The fermentability of xylose from the hemicellulosic hydrolysate was further evaluated for succinic acid production.